IMPLEMENTASI CHATBOT DIAGNOSA PENYAKIT PADA KUCING DAN ANJING DENGAN METODE FORWARD CHAINING - Bagas Krinasia Putra (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2023)
Currently, many people have made pets as pets and even treat them like humans, even considering pets as family. Among the various kinds of pets, cats and dogs are the most common pets. Cats and Dogs are animals that are popular among the public, their cute physical shape and adorable behavior is one of the reasons why many people like these pets. in the current technological developments that can provide information related to animal diseases, especially dogs and cats and how to provide first aid if the two animals are sick and provide a means for pet owners to get information quickly by implementing a chatbot based on Natural Language Processing and the application of an expert system which is a sub-field of artificial intelligence (Artificial Intelligence) with the forward chaining method. It is hoped that with the chatbot pet owners can find it easier to get answers quickly about their dog and cat diseases. Keywords : Artificial Intelligence, Chatbot, Forward Chaining , NLP (Natural Language Processing).